Cross-Cultural Comparative Analysis of Technological Gap between Tribal Pineapple Growers of Meghalaya, India - Marak, Balkho Rangsa; Watt, Haobijam James; Lahiri, Biswajit; Syiem, Rebekka; Bandyopadhyay, Arup Kumar (Indian Journal of Extension Education, 2022)
The varied agro-climatic condition of Meghalaya favours cultivation of different horticultural crops, particularly different fruit crops, and pineapple is the most notable of them. The present study was conducted on 200 tribal pineapple growers of Meghalaya in the North Eastern Himalayan region of India in the year 2017-2018. The article highlighted the technological gap among pineapple growers with special emphasis on the differences in agro-economic, socio-psychological and extension-communication characteristics between the Khasi and the Garo tribes of Meghalaya in the north-eastern Himalayan region of India. The average level of the technological gap of Garo farmers (61.78%) was slightly higher than that of Khasi farmers (57.85%). The Mann-Whitney U test reported that the mean scores of the technological gap for the farmers of West Garo Hills and Ri Bhoi were indicating a significant difference in the technological gap between the farmers of these two tribes. The study suggested the need to understand the differential characteristics of these tribes and to introduce location-specific technologies to minimize the technological gap and increase pineapple production in these tribal areas.
Keywords: Technological gap; Tribal communities; Pineapple growers; Agro economic; Extension-communication; Socio-psychological